Enrichment of Genetic Variants in the Glucocorticoid Receptor Signalling Pathway in Autoimmune Hepatitis with Failure of Standard Treatment. Issue 3 (18th May 2017) - Eriksen, Peter Lykke; Kreutzfeldt, Martin; Grønbæk, Henning; Thorsen, Kasper; Vang, Søren; Jessen, Niels; Vilstrup, Hendrik
Abstract: The standard treatment for autoimmune hepatitis (AIH) is predniso(lo)ne for remission induction, tapered and followed by azathioprine, which effectively controls the disease in the majority of patients. However, some patients prove to be unresponsive or non‐tolerant and require alternative immunosuppressive regimens for disease control. We aimed to investigate whether these AIH patients who experience failure of standard treatment have a genomic basis for their problem in the form of pharmacogenetic variants. Fifty‐six consecutive patients with AIH [41 female and 15 male; median age 42 years (12–76)] were retrospectively stratified according to being responders to standard therapy (n = 33) or patients with failure of standard therapy (n = 23). Their blood DNA was exome‐captured and sequenced. Genomic variants were filtered and compared between the groups using Ingenuity Variant Analysis (3.1.20150407). The exome sequencing and data processing revealed glucocorticoid receptor signalling to be the most prominently affected pathway among the patients with failure of standard therapy (highly significant). Standard treatment failure was not associated with thiopurine S ‐methyltransferase variants or the HLA‐DRB1*03 genotype. In conclusion, enrichment of variants related to glucocorticoid receptor signalling was a particular genomic trait of the AIH patients in whom standard treatment failed and alternative immunosuppression was required. If confirmed, a future application of this finding may be to identify prospective cases of failure of standard treatment already at diagnosis.